Interpreting the development and growth of convict criminology in South America - Ross, Jeffrey Ian (2018)
The Convict Criminology (CC) network has expanded beyond its American and Canadian roots to the United Kingdom and Europe. Although increasing documentation of CC’s activities and scholarship built upon CC has been produced in these countries and region, less well known are efforts beyond these locations. This article reviews attempts to build a network of scholars who are interested in the growth of Convict Criminology in South America. It may also serve as a discussion paper for a possible conference to be held in São Paulo, Brazil, Santiago de Chile, or Quito, Ecuador in the near future. The balance of the article reviews some of the dynamics for the conference.